Social Neuroscience and Public Health Foundations for the Science of Chronic Disease Prevention - Hall, Peter A. (Springer New York : Imprint: Springer, 2013)
Traditionally, neuroscience and public health have been considered strange bedfellows.  Now a new collection of studies shows the two fields  as logical collaborators with major potential for the evolution of both fields. Social Neuroscience and Public Health assembles current theoretical viewpoints, research findings in familiar and emerging areas, and updates on assessment methods to give readers a unique in-depth guide to the social brain and its central role in health promotion. This stimulating reference spans the intersection of two disciplines, offering new insights into the mechanics of risks, rewards, and willpower, revisiting the developmental effects of adversity and the impact of exercise on brain health, and applying epidemiology to cognitive science. Accessibly written for researchers and professionals within and outside both fields, the chapters include bullet-point and policy implication features for ease of retention. The book's innovative ideas lend themselves to a variety of applications, from fine-tuning disease prevention strategies to deeper understanding of addictions. Included in the coverage: Latest theoretical perspectives on health behavior (e.g., picoeconomics, MCII, and temporal self-regulation theory) Updates on health communications and their effects on the brain. New research on cognitive resources and health behavior execution. Leading-edge studies on the brain, the social world, and stress. Findings from the forefront of exercise neuroscience. A concise introduction to neuroscience methods for the non-technical reader. A rich resource pointing to a promising future in research and prevention efforts, Social Neuroscience and Public Health benefits professionals and researchers in public health, medicine, cognitive neuroscience, health psychology, epidemiology, sociology and affiliated fields. "This bridge-builder of a book comes exactly at the right time. With the field of public health rapidly expanding, public health professionals, neuroscientists, social psychologists, and policymakers alike will profit from this immensely integrative achievement. Social Neuroscience and Public Health connects two fast-developing fields that can learn and profit immensely from each other." -- Wilhelm Hofmann, PhD, University of Chicago, Booth School of Business   "In this book you will find a number of intriguing possibilities for changing behaviour that arise out of a scientific base hitherto little known beyond the field. Bringing this together has immense potential not just for strengthening public health but also for strengthening behavioral and neuro-sciences." -Theresa Marteau, PhD, Institute of Public Health, Unviersity of Cambridge.